Uji Aktivitas Penghambatan Enzim α-Amilase dan Glukoamilase dari Ekstrak Etanol Daun Kirinyuh (Chromolaena odorata L.) - Nelson Gaspersz; Eirene Grace Fransina; Anancy Reza Ngarbingan (JURNAL KIMIA MULAWARMAN, 2022)
Research has been carried out to test the inhibitory activity of α-amylase and glucoamylase enzymes in the ethanolic extract of kirinyuh (Chromolaena odorata L.) leaves. The use of kirinyuh leaf ethanol extract as a diabetes drug in vivo has been carried out, but its mechanism of action have never been researched before, so further research is needed on the specific mechanism of ethanolic extract of kirinyuh leaves in reducing blood sugar levels, especially through inhibition of α-amylase and glucoamylase enzymes in vitro. The purpose of this study was to test the antidiabetic activity of the ethanol extract of kirinyuh leaves in vitro using α-amylase and glucoamylase inhibition methods. This research uses DNS spectrophotometric method. The results showed that kirinyuh leaf ethanol extract proved to have inhibitory activity against α-amylase and glucoamylase enzymes with IC50 values of 3730.15 ± 28.91 ppm or 3730.15 ± 28.91 µg/mL and 2510.78. ± 383.37 ppm or 2510.78 ± 383.37 µg/mL. From the results, it can be concluded that the ethanolic extract of kirinyuh leaves has inhibitory activity against α-amylase and glucoamylase enzymes. Telah dilakukan penelitian uji aktivitas penghambatan enzim α-amilase dan glukoamilase ekstrak etanol daun kirinyuh (Chromolaena odorata L.). Penggunaan ekstrak etanol daun kirinyuh sebagai obat diabetes secara in vivo telah dilakukan,tetapi belum diketahui mekanisme kerjanya, sehingga perlu dilakukan penelitian lebih lanjut mengenai mekanisme spesifik ekstrak etanol daun kirinyuh pada penurunana kadar gula darah terutama melalui aktivitas penghambatan terhadap enzim α-amilase dan glukoamilase secara in-vitro. Tujuan penelitian ini untuk untuk menguji aktivitas antidiabetes ekstrak etanol daun kirinyuh secara in vitro menggunakan metode penghambatan enzim α-amilase dan glukoamilase. Penelitian ini menggunakan metode DNS secara spektrofotometri. Hasil penelitian menunjukkan ekstral etanol daun kirinyuh terbukti memiliki aktivitas penghambatan terhadap enzim α-amilase dan glukoamilase dengan nilai IC50 masing-masing, yaitu sebesar 3730,15 ± 28,91 ppm atau 3730,15 ± 28,91 μg/mL dan 2510,78 ± 383,37 ppm atau 2510,78 ± 383,37 μg/mL. Dari hasil dapat disimpulkan bahwa ekstrak etanol daun kirinyuh memiliki aktivitas penghambatan terhadap enzim α-amilase dan glukoamilase.